Circulation patterns of Ría de Pontevedra under upwelling and downwelling conditions - Rodríguez Cruz, Elisabet (2018)
Circulation patterns inside some of the Rías Baixas have been widely studied, but this is not the case of the Ría de Pontevedra. Through this thesis, we try to enhance the knowledge about the circulation pattern of this Ría. A ROMS-AGRIF system con guration was used in this study. This con guration was validated through the comparison with weekly temperature and salinity data measured by INTECMAR. The analysis done in this work is based on the study of three representative events of the circulation patterns: one upwelling event and two downwelling events, one of them with Lérez river ow increase. Also, was analyzed temporal series of uxes and ushing times through the external mouths and the correlations between these series and the forcing parameters (winds and average of the rivers ow). An EOF's study was applied to the subinertial normal velocities at the sections. Upwelling events are characterized by a reinforcement of the positive estuarine circulation, consistent with surface layer out ows and deep layer in ows at the main channel of the Ría, and in ows/out ows at the north/south mouths. Downwelling events have an opposite behaviour to the event described before. There are evidences of the vertical mixing through clockwise circulations at the outer part of the Ría, associated with the ocean waters subduction that enter into the Ría through the surface layer. As a consequence, a blocking can be generated at the middle part of the Ría, which has been associated by other authors with the "red tides". Fluxes for downwelling events are higher than for upwelling events. Flushing times are around 2 days for downwelling and around 4 days for upwelling events. The EOF's study con rms the circulation described for upwelling and downwelling events, in this work. The forecast of the physical conditions at Ría de Pontevedra are important for the understanding of the processes behind the production of HABs.